2008
DOI: 10.1007/s11695-007-9357-y
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery: Low Mortality at a High-Volume Center

Abstract: Surgeons at Hackensack University Medical Center, a high volume, accredited 1A American College of Surgeons Bariatric Surgery Center, achieved a 0.13% mortality among 5,365 patients undergoing weight loss operations between 1998 and June, 2006. This study supports the concept that high-volume centers perform bariatric operations with low mortalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 36 publications
(45 reference statements)
2
24
0
3
Order By: Relevance
“…The impact and value of this policy decision has been questioned and the main mechanism of its effect (procedure shift, patient risk shift or center accreditation status-effect) has not been well explored. While studies at single centers (20) and across multiple centers (21)(22)(23) have demonstrated a positive impact of COEs on outcomes, others have found no improvements, (24,25) but decreased access to care. (26,27) One significant problem in assessing the impact of the NCD is the difficulty of separating out the effect of temporal trends, improvements in surgical techniques, shifts to safer procedures, and changes in patient population from the effect of the center's accreditation status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact and value of this policy decision has been questioned and the main mechanism of its effect (procedure shift, patient risk shift or center accreditation status-effect) has not been well explored. While studies at single centers (20) and across multiple centers (21)(22)(23) have demonstrated a positive impact of COEs on outcomes, others have found no improvements, (24,25) but decreased access to care. (26,27) One significant problem in assessing the impact of the NCD is the difficulty of separating out the effect of temporal trends, improvements in surgical techniques, shifts to safer procedures, and changes in patient population from the effect of the center's accreditation status.…”
Section: Discussionmentioning
confidence: 99%
“…A "volume-outcome" relationship in bariatric surgery has been controversial with studies demonstrating benefit, (20,(28)(29)(30)(31) especially in the early case volume of a surgeon (6) while others have questioned this relationship and called for using risk-adjusted outcomes, independent of volume for accrediting COEs. (32)(33)(34) There may be other mechanisms by which the NCD may have exerted a center effect other than through shifts to higher volume hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Furthermore, it is important to note in the context of the current series and with the recognition that these procedures were carried out under the supervision of experienced surgeons, that the complexity of the surgery did not translate into increased surgical complications or poorer oncological outcomes (PSM or BCR rates). Interestingly, two recent studies found a higher risk of vesico-urethral strictures in obese men undergoing RP.…”
Section: Discussionmentioning
confidence: 96%
“…These improvements have also been reflected in other surgical spheres. 14,15 Additionally, recent reports from Europe suggesting that oncological outcome is not dependent on BMI 16,17 have challenged the belief that higher BMI patients have poorer disease-related outcomes. Thus, it stands to reason that earlier experiences of poor outcomes in obese patients might now be reduced with refinement of technique and experience operating in this subgroup of patients.…”
Section: Introductionmentioning
confidence: 99%
“…En los últimos 15 años, hemos logrado establecer un programa de tratamiento quirúrgico de la obesidad, con excelentes resultados a largo plazo, con una tasa de complicaciones comparables con las grandes series publicadas en la literatura mundial [29][30][31][32][33][34][35] . En nuestra experiencia, la mortalidad global postoperatoria es de 0,04%.…”
Section: Discussionunclassified